PENGARUH POLA ASUH ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS X DI SMK DIPONEGORO SALATIGA - simaremare, Raisha; Tritjahjo Danny Soesilo; Maya Rahadian Septiningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of parenting styles on the learning motivation of Grade X students at SMK Diponegoro. The parenting styles examined in this study are based on Diana Baumrind’s (1966) theory, which includes authoritarian, authoritative (democratic), and permissive parenting styles. The research method used is quantitative with a simple linear regression approach. The sample consisted of 102 students selected through purposive sampling. The results showed that parenting styles significantly influence students’ learning motivation. The regression analysis revealed an R Square value of 0.932, indicating that 93.2% of the variation in learning motivation can be explained by parenting styles. Among the three types of parenting analyzed, the authoritative (democratic) style had the most dominant and significant influence on students’ motivation. In contrast, authoritarian and permissive parenting styles did not show significant effects. These findings align with Baumrind’s theory, which suggests that the authoritative parenting style balancing control and warmth tends to encourage children to be independent and motivated in learning.